Optical properties, plasmons, and orbital Skyrme textures in twisted TMDs - Lorenzo Cavicchi; Koen J. A. Reijnders; Mikhail I. Katsnelson; Marco Polini (npj Quantum Materials)
Abstract In the long-wavelength limit, Bloch-band Berry curvature has no effect on the bulk plasmons of a two-dimensional electron system. In this Letter, we show instead that bulk plasmons are a probe of real-space topology. In particular, we focus on orbital Skyrme textures in twisted transition metal dichalcogenides, presenting detailed semiclassical and quantum mechanical calculations of the optical conductivity and plasmon spectrum of twisted MoTe2.